Master's Programme in Urban and Regional Planning (Interuniversity Department of Regional and Urban Studies and Planning, Politecnico di Torino) - Di Marino, Mina; Silva, Paulo; Dabović, Tijana; Cotella, Giancarlo (AESOP, 2024)
The MSc in Urban and Regional Planning delivered at the Politecnico di Torino stands out for its two tracks: i) Pianificare la città e il territorio per la transizione ecologica (PCT) - Urban and Regional Planning for Ecological Transition - and ii) Planning for the Global Urban Agenda (PGUA); which are provided in Italian and English, respectively. The PCT track focuses on training professionals who mainly operate within the Italian regulatory framework but who are aware of international changes and policies, while the PGUA focuses on training practitioners able to operate within the world planning market, by focusing on current global challenges, which are identified by the UN 2030 Agenda. Programme Curriculum and Identity - The master program is recognized for its high degree of interdisciplinarity (ensured by the teaching staff from several disciplines) and offers a range of studios as multi-disciplinary modules. the following: i) an extensive use of GIS in several courses such as transportation systems and mobility, and ii) a geographical lens to interpret socio-spatial phenomena. - Several environmental and social issues are addressed in several courses and studios. In addition, the contribution of public officers and stakeholders in the classes is relevant for framing and discussing about real cases. Principles of Pedagogy • Learning by doing is predominant in the program. Students are exposed to ethical dilemmas in close to real-life contexts. There is also a strong stimulus to independent and group learning, and to reflexive praxis in their pedagogical practices. • Learning from and with diversity inspires students to group learning. Students are also stimulated to explore research and inquiry taking advantage of their background and of cross-disciplinarity. • Apprehending from different perspectives occurs through students’ exposure to spatial foci, through regional and urban scales, and in an inter-scalar approach; global contexts, providing in both tracks environments that stimulate global comprehension of spatial planning phenomena; contemporary socio-spatial challenges related to ecological transition and UN 2030 Agenda; transition from theory to practice stimulating practical reasoning and judgement.